Popularisierung im (fachsprachlichen) Translationsunterricht – ein Aspekt der Translationsdidaktik - Feyrer, Cornelia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper presents some approaches to and results of working with and integrating various text types of popular medical texts, as experienced when teaching translation. The premise for this work is the concept that popular-ized texts are still technical texts and can therefore be horizontally diversified and vertically stratified depending on their technical level. This, in com-bination with the practical framework set by the task and the persons involved in the interaction, makes various demands on the translator, who is called upon not only to provide a transcultural and inter-language transla-tion of a technical text, but also to respect the specific circumstances of the target public at whom the target text is aimed. This is necessary for skopos-oriented adaptation of the source material.